2021
DOI: 10.1002/cam4.3940
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection and survival outcomes in metastatic young adult colorectal cancer patients

Abstract: Background The incidence of colorectal cancer in adults younger than age 50 has increased with rates expected to continue to increase over the next decade. The objective of this study is to examine the survival benefit of surgical resection (primary and/or metastatic) versus palliative therapy in this patient population. Methods We identified 6708 young adults aged 18–45 years diagnosed with metastatic colorectal cancer (mCRC) from 2004 to 2015 from the SEER database. Overall survival (OS) was analyzed using K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…For those with initially non-resectable metastasis, current guides suggested that systemic chemotherapy should be administrated first to achieve secondary resection 22 . In this study, our analysis suggested that metastasectomy was an independent prognostic factor for survival, which was similar to the results of previous studies 23 , 24 . However, whether metastasectomy should be performed simultaneously with primary cancer or should be delayed remains controversial 25 , 26 .…”
Section: Discussionsupporting
confidence: 92%
“…For those with initially non-resectable metastasis, current guides suggested that systemic chemotherapy should be administrated first to achieve secondary resection 22 . In this study, our analysis suggested that metastasectomy was an independent prognostic factor for survival, which was similar to the results of previous studies 23 , 24 . However, whether metastasectomy should be performed simultaneously with primary cancer or should be delayed remains controversial 25 , 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Due to the substantial improvements of multimodal therapies, several metastatic neoplasms can be treated by surgery. For example, resections have been successful to improve the survival of metastatic colorectal carcinoma and neuroendocrine neoplasms in selected patients (24)(25)(26). However, the benefit of surgery for metastatic MiNENs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The study emphasized that colorectal cancer cases should be diagnosed early to perform surgery, which is known to have a significant impact on survival, and in this respect, the importance of regular screening of healthy individuals. In another recent study, Arhin et al 22 examined the relationship between surgical resection and survival outcomes in young patients diagnosed with colorectal cancer and found that resection of both primary tumors and metastases separately increased survival in colorectal cancers independently of all other variables. It was found to increase the duration.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of studies investigating the prognostic value of pre-treatment CA 19-9 levels in colorectal cancer cases reported that CA 19-9 level is associated with overall survival and progression-free survival time and can predict mortality. [22][23][24][25] The increase in CA 19-9 level is associated with the formation of tumor cell-induced platelet aggregation, a necessary process that plays a role in distant metastasis of colorectal cancer. It has been reported that CA 19-9 level recorded at diagnosis is a prognostic factor independent of other variables in metastatic colorectal cancers, it can predict bevacizumab efficacy and is associated with KRAS/BRAF mutation status.…”
Section: Discussionmentioning
confidence: 99%